Peran Mesjid dalam Meningkatkan Akses Pendidikan bagi Masyarakat : Solusi untuk Tantangan Zaman - Naura Azifa; Sri Wahyuni; Aliza Aliza; Badri Badri; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study examines the role of mosques in improving access to education for the community, focusing on the solutions offered in facing the challenges of the times. Mosques, which have been known as places of worship, also function as vital education centers, both for religious education and practical skills. The research method used is descriptive qualitative, with data collection through in-depth interviews, observation, and documentation studies in several mosques in urban and rural areas. The results show that mosques play an active role in providing inclusive education and empowering communities, especially vulnerable groups. The educational programs implemented in mosques not only improve people's literacy and skills, but also strengthen positive social and cultural values. The findings are expected to provide insights into the contribution of mosques in creating sustainable solutions for access to education, as well as educating future generations who are competitive and characterized.